Enhanced vs. standard low dose dexamethasone treatment on respiratory outcomes of preterm infants with bronchopulmonary dysplasia - Gunes, Sezgin; Sahin, Suzan; Bozkurt, Ozlem; Cezayir, Begum; Bozgul, Arda; Gonulal, Deniz; Oncel, Mehmet Yekta (Frontiers in Pediatrics, 2025)
BackgroundPremature infants are particularly vulnerable to complications such as bronchopulmonary dysplasia (BPD). Although systemic steroids have been used for some time, no effective alternative treatments have emerged. This has led clinicians to investigate various dosing regimens and discuss the necessity of revising systemic steroid dosages. This study aims to evaluate the effectiveness and safety of two different doses of systemic dexamethasone use in treating BPD in premature infants born at or below 30 weeks of gestation.MethodsA retrospective review was conducted on hospital records of premature infants admitted to the Neonatal Intensive Care Unit of Izmir Private Medicalpark Hospital for a 6-year period. In the first 2 years of these 6 years, as historical controls, infants with evolving BPD had received dexamethasone treatment according to the DART protocol, while the ones born in the last 4 years received enhanced low-dose treatment. Data collected included demographic characteristics, risk factors for preterm birth, duration and way of oxygen support, prematurity-related complications, systemic dexamethasone doses, and mortality.ResultsOf the 368 infants analyzed in the study, 265 had received systemic enhanced low dose dexamethasone, while 103 had received low dose dexamethasone treatment. Baseline characteristics including gestational age, birth weights, and RDS severity were similar among groups The study found that a cumulative dose of 1.35 mg/kg of systemic dexamethasone (enhanced low dose) is both safe and more effective than standard low dose dexamethasone (DART protocole) therapy in the management of BPD. The DART group required significantly longer invasive and non-invasive ventilatory support compared to the enhanced low-dose group. By the 36th gestational week, a higher proportion of infants in the enhanced low-dose group were free from oxygen support. The enhanced low-dose group also had a higher extubation success rate. Dexamethasone -related side effects were minimal, with only two cases of hypertension and one of interventricular septal hypertrophy in the enhanced low dose group, and one case of hypertension in the DART group, all resolving over time.ConclusionsOur study suggests that an enhanced low-dose dexamethasone regimen (1.35 mg/kg) may offer superior respiratory outcomes compared to the conventional DART protocol without a significant increase in short-term adverse effects.